Pengaruh Peran Penyuluh Pertanian Terhadap Dinamika Kelompoktani Hortikultura di Kecamatan Tigapanah - Ompu sunggu, Esterida Br; Arifudin, Arifudin; Rosnita, Rosnita (Fakultas Pertanian Universitas Jember, 2023)
The dynamics of farmer groups is influenced by internal factors, namely the farmer groups themselves and external factors. Namely the role of agricultural extension workers. This research was conducted in Tigapanah District, Karo Regency with the consideration that this sub-district had the second largest number of farmer groups in Karo Regency with a total of 349 farmer groups. This study aims to analyze the effect of the role of agricultural extension workers on the dynamics of horticultural farmer groups. The analytical method used is Structural Equation Modeling (SEM) analysis. The results showed that the role of agricultural extension workers as facilitators, innovators, motivators, dynamists, educators, and consultants had a significant effect on the dynamics of horticultural farmer groups consisting of group objectives, group structure, task functions, group coaching and development, group cohesiveness, group atmosphere, group pressure, group effectiveness, and ulterior motives.